ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI KARET DI KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Simamora, Dinsa Iman Sari; Dewi, Novia; Yusri, Jum’atri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is (1) knowing performance of rubber farm effort of rubber in Pangkalan Kuras District Pelalawan Regency (2) Analyze the dominant factors that influences the citizen’s production rate of rubber in Pangkalan Kuras District Pelalawan Regency compare during September 2015 until Mei 2017 in Pangkalan Kuras District Pelalawan Regency. This research used survey method at two central rubber production villages in Pangkalan Kuras District Pelalawan Regency (Sorek Dua village and Dundangan village). The sampling technique used simple random sampling.The result of this study conclude : (1) the performance of farm effort of rubber in Pangkalan Kuras District is : wide of farmers rubber average 2 ha, average’s rubber age is 22nd years old, total’s rubber average is 549 trees/ha, total devote of labor average is 209.97 HKP/ha/year to consist of 44.37% (TKDK)  and 55.62% (TKLK), The average of herbisida give is 83.37 liter/ha/tear, average of production is 2985 kg/ha/year. The production factor of rubber farm effort in Pangkalan Kuras District consist of land wide, labor, herbisida, manure, and seet. In this research the farmer aren’t do the fostering because they have the equity’s limited. (2) production factor that significant to rubber on 20% of real standard are plant’s age, plant’s total, devote’s labor and herbisida.Keywords: Dominant Factor, Performance, Rubber Production